Theoretical Bases for the Historical Study of the "Oppida Veteris Latii" of "Hispania" - Espinosa Espinosa, David (Gerión. Revista de Historia Antigua, 2018)
This work aims to contribute to the creation of new theoretical bases for the study of the oppida veteris Latii in Hispania. These Hispanian towns, mentioned only by Pliny the Elder in his Naturalis historia, cause an important historical (and historiographical) problem due to their chronological origin and legal-administrative nature. The first part of this paper is concerned on the definition of the study question, followed by an overview of the interpretations made by scholars on both issues. As these are proven to be invalid, mainly because of their inherent contradictions, an alternative historical explanation is proposed, basing on a thorough Pliny the Elder’s account analysis. The result is a new research hypothesis, which explains the existence of the oppida veteris Latii in Hispania on the basis of an old group of Republican Latin colonies which were changed into municipia Latina by Augustus. Finally, a chronological framework for the context in which this administrative change could have taken place is provided.